Synthesis, structural and mass spectrometric investigations of pyridinium bis(thiosalicylato)mercurate(II) - Henderson, William; Thomas, Jesse C.; Okpareke, Obinna C.; Tiekink, Edward R. T. * (Elsevier, 2019)
The previously-described bis(thiosalicylato)mercury(II) complex [Hg(SC6H4-2-CO2H)2],prepared from HgCl2 and thiosalicylic acid (HSC6H4-2-CO2H) with added NaOH, dissolves in pyridine (py), from which the crystalline pyridinium salt (pyH)2[Hg(SC6H4-2-CO2)2] can be isolated as large colourless blocks. Single crystal X-ray crystallography reveals the crystal to comprise two distinct three-molecule aggregates, namely {Hg[SC6H4-2-C(=O)OH]2(NC5H5)2} and {Hg[SC6H4-2-C(=O)O]2(HNC5H5)2}, which differ in the location of the acidic hydrogen atoms, i.e. either compound-bound for the former species or located on the pyridinium cations in the latter. The thiolate ligands are S,O-chelating and the resultant O2S2 four-coordinate geometries are each based on a distorted disphenoidal geometry. The three-molecule aggregates are sustained by hydroxyl-O‒H…N(pyridine) hydrogen bonds in the case of {Hg[SC6H4-2-C(=O)OH]2(NC5H5)2} whereas the second aggregate features charge-assisted pyridinium-N‒H…O(carboxylate) hydrogen bonds. These aggregates are connected into a three-dimensional architecture by a combination of C‒H…O, π…π, Hg…π and O…π interactions. (pyH)2[Hg(SC6H4-2-CO2)2] was also characterised by negative-ion ESI mass spectrometry, where it showed appreciable stability towards capillary exit voltage-induced fragmentation. In contrast, the S-bonded monodentate thiosalicylate complexes RHg(SC6H4-2-CO2) - (R = Et, Ph or ferrocenyl) undergo facile decarboxylation at relatively low voltages, with the phenyl and ferrocenyl complexes subsequently forming RHgSas an additional fragment ion at high voltages. Aggregate ions formed with the sodium counter-cations of the type [(RHgSC6H4-2- CO2)nNan-1] - show appreciable stability towards fragmentation.